Geology of Uranium Lake City, Cinch Mines, Saskatchewan - A Turek (Canadian Institute of Mining, Metallurgy and Petroleum, 1965)
The Lake Cinch deposit occurs in the Tazin gneisses on the footwall side of the Black Bay fault. Ore is localized by two faults, the Main Ore fault and the Cracking-stone River fault, occurring in shoots along the former and on tension fractures between the two faults. Faulting leading to the localization of the deposit is analyzed in detail and tied into the regional pattern. Pitchblende, the chief radioactive mineral, is investigated by X-ray and found to be of very small particle size. The relation-ships of U, Fe and Mn in the ore are established quantitatively, and Fe is found to bear a catalytic relation to U. The deposit is classed as belonging to Lindgren's mesothermal class. Mineralization is attributed to carbonate solutions, and the uranium is believed to have been trans-ported in the hexavalent state as the uranyl tricarbonate ion; analogy is drawn to a recently developed hydro-metallurgical technique for the production of uranium dioxide. Introduction THE Lake Cinch deposit is located in the Beaver-lodge Camp, Saskatchewan. The property was staked in 1948 and went into production in 1957